2022
DOI: 10.3390/ani12172204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Production Systems and Seasons on Retail-Goat-Milk Fatty-Acid Composition and Nutritional Indices in Greece

Abstract: An increased consumer interest in goat milk has been registered in recent years due to its health-related benefits. This study aimed to investigate the effects of production systems and seasons on fatty-acid composition and nutritional indices for the healthy fat consumption of retail goat milk. The study lasted one year, and milk samples (n = 160) from 14 brands (10 conventional and 4 organic) were collected on a monthly basis. Organic milk had a marginally lower fat and protein content compared with conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
1
5
2
Order By: Relevance
“…Barłowska et al [49] also observed significantly lower AI and TI values in the milk of goats that grazed in mountainous regions during the day and received concentrate supplementation during milking. The values of both indices are lower than the ones reported by Kasapidou et al [15] on retail goat milk during spring, summer, and autumn. Furthermore, sampling period did not affect (p > 0.05) the hypocholesterolaemic: hypercholesterolaemic (h/H) ratio, which is employed to represent the relationship between the hypocholesterolemic and the hypercholesterolemic fatty acids, and high values are desirable.…”
Section: Milk Fatty Acid Composition and Nutritional Valuecontrasting
confidence: 81%
See 2 more Smart Citations
“…Barłowska et al [49] also observed significantly lower AI and TI values in the milk of goats that grazed in mountainous regions during the day and received concentrate supplementation during milking. The values of both indices are lower than the ones reported by Kasapidou et al [15] on retail goat milk during spring, summer, and autumn. Furthermore, sampling period did not affect (p > 0.05) the hypocholesterolaemic: hypercholesterolaemic (h/H) ratio, which is employed to represent the relationship between the hypocholesterolemic and the hypercholesterolemic fatty acids, and high values are desirable.…”
Section: Milk Fatty Acid Composition and Nutritional Valuecontrasting
confidence: 81%
“…Finally, Žan et al [41] found a better fatty acid composition in milk from a mountain flock consisted of goats of Alpine breed grazing at an altitude of 1060-1075 m in comparison to milk from a highland flock consisted of goats of the Saanen breed grazing at an altitude of 615-630 m. In general, pasture feeding can affect milk fatty acid composition, but it is dependent on parameters such as the type of forage, variation in pasture availability, and stage of grass growth maturity [6,42]. The fatty acid composition during the entire study period is within the range reported by Kasapidou et al [15] on retail goat milk on an annual basis.…”
Section: Milk Fatty Acid Composition and Nutritional Valuesupporting
confidence: 60%
See 1 more Smart Citation
“…In goat milk, the PUFA/SFA ratio ranges from 0.04 to 0.18, the n-6/n-3 ratio from 1.49 to 6.60, the AI ratio from 1.89 to 2.77, the TI ratio from 2.04 to 3.20, and the LA/ALA ratio from 1.15 to 10.67 [21,38,40,41]. The PUFA/SFA and LA/ALA ratios detected in our study were in the range, whereas the other indicators were lower.…”
Section: Fatty Acid Summaries Ratios and Indexesmentioning
confidence: 99%
“…The FA composition, as a measure of the quality of raw milk used in the production of milk and dairy products from goats, may vary depending on the breed (Martinez et al, 2011;Curro et al, 2019), dietary sources of fat (Ayeb et al, 2015;Kholif et al, 2016), nutrition and management (Haile et al, 2016), stage of lactation (Curro et al, 2019), production system (Lopez et al, 2019), and season (Kasapidou et al, 2022). Milk FAs have been reported for transboundary breeds (i.e., breeds found in more than one country) such as Alpine goats in Italy (Lopez et al, 2019), Anglo Nubian in Egypt (Kholif et al, 2016), and Saanen in China (Haile et al, 2016), Estonia (Yurchenko et al, 2018), and Italy (Curro et al, 2019), and local breeds (i.e., breeds found in only one country) -including the indigenous goat breeds in Italy -Garganica, Girgentana, Jonica, Maltese, and Mediterranean Red (Curro et al, 2019) and in Tunisia (Ayeb et al, 2015), Malagueña goats in Spain (Martinez et al, 2011), native goats in Greece (Kondyli et al, 2012), Peranakan Etawah goats in Indonesia (Sumarmono & Sulistyowati, 2015), and Swedish Landrace goats in Estonia (Yurchenko et al, 2018).…”
Section: Introductionmentioning
confidence: 99%